Effects of vitamin D supplementation on fasting glucose, dyslipidemia, blood pressure, and abdominal obesity among patients with metabolic syndrome: a protocol for systematic review and meta-analysis of randomized controlled trials - Séphora Louyse Silva Aquino; Aline Tuane Oliveira Cunha; Josivan Gomes Lima; Karine Cavalcanti Maurício Sena-Evangelista; Antonio Gouveia Oliveira; Ricardo Ney Cobucci; Lucia Fatima Campos Pedrosa (Systematic Reviews, 2020)
Abstract Background Vitamin D deficiency can play a role in extraskeletal functions that are involved with a set of risk factors associated with metabolic syndrome (MetS). The purpose of this review is to investigate the impact of vitamin D supplementation on fasting glucose, dyslipidemia, blood pressure, and abdominal obesity among patients with MetS. Methods EMBASE, Medline, Web of Science, Lilacs, the Cochrane Central Register of Controlled Trials, clinicaltrials.gov databases, and grey literature will be systematically searched for randomized controlled trials (RCTs) of vitamin D supplementation compared with placebo, through December 2020. We will include in the study patients with MetS diagnosed by the criteria set forth by the National Cholesterol Education Program Adult Treatment Panel III or the International Diabetes Federation. The effect of oral vitamin D supplementation on lipid profile improvement (triglycerides, high-density lipoprotein cholesterol—HDL-C) is this review’s primary outcome. The systematic review will be performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The study screening, data extraction, and quality assessment will be fulfilled by two independent reviewers according to the Cochrane Risk of Bias tool (RoB 2.0). The results of the systematic review will be provided according to the type of intervention, characteristics of the target population, the methods of measurement of vitamin D, the calculated vitamin D concentrations, types of biological samples, and types of outcomes. Meta-analyses will be conducted where appropriate. The Cochran’s Q test and the I 2-heterogeneity test will be used to assess the presence of heterogeneity and whether the fixed or the random-effects model would be appropriate for combining study results using the inverse variance method or the DerSimonian-Lair method, respectively. Publication bias will be evaluated using funnel plots and Egger’s and Begg’s tests. The strength of the evidence will be assessed according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Discussion This systematic review will assess the effects of vitamin D supplementation on fasting glucose and triglyceride levels, waist circumference and mean blood pressure, and HDL-C among individuals with MetS. These findings may assist with decision-making within a clinical setting. Systematic review registration PROSPERO registration number CRD42019123212